THE REPRESENTATION OF DISEASE AMONG THE ROMA POPULATION IN NORTH-EASTERN ROMANIA - SOPONARU, Camelia; SEMENIUC, Suzana; IOAN, Beatrice-Gabriela; IORGA, Magdalena (Studia Universitatis Babeş-Bolyai Bioethica, 2015)
In the context of the new challenges of globalization, the Roma ethnic group, internationally considered a disadvantaged minority, at the edge of subsistence, regardless of the country of residence, is permanently a topic of study in various scientific fields. One of the representative fields of everyday life on which this paper focuses is that of disease and, implicitly, that of health. Previous studies having tackled the same problematics suggest that, if in the past the social representation of health and illness among Roma people was deeply impregnated with traditions and with the type of magical thinking so characteristic of this ethnicity, at present, this social representation has undergone major changes. More exactly, scientific explanations of disease have taken the place of mystical ones, and the trust in traditional healing practices has lost ground to medical procedures and medication. The research has set out, on the one hand, to identify the social representation of disease among the Roma population and, on the other hand, to establish whether this has undergone important changes in recent years, under pressure from social representations of health and disease among the majority population. Following the analysis of the carried out interviews, we may conclude that, though many elements of the central nucleus of social representation are maintained, such as disease regarded as a divine punishment, superstitions, traditional healing methods or marks of magical thinking, one notices the penetration of new elements in everyday language: causes of diseases from the medical register, diagnoses or medical treatments. In addition, an important aspect is the way in which the doctor-patient relationship has evolved, currently being almost totally freed from constraints imposed by traditional beliefs. Reprezentarea bolii în rândul populației rome din regiunea de nord-est a României. În condițiile noilor provocări ale globalizării, grupul etnic al Romilor, considerat pe plan internațional o minoritate dezavantajată, la limita subzistenței, indiferent de țara de rezidență, este un permanent subiect de studiu în variate domenii științifice. Unul dintre domeniile reprezentative pentru viața de zi cu zi, pe care se axează această lucrare, este cel al bolii și, implicit, al sănătății. Studii anterioare care au abordat aceeași problematică, sugerează că dacă în trecut, reprezentarea socială a sănătății și bolii în rândul Romilor era profund impregnată de tradiții și tipul de gândire magică atât de caracteristic acestei etnii, în prezent a suferit modificări majore. Mai exact, explicațiile științifice ale bolii au luat locul celor mistice, și încrederea în practicile de vindecare tradiționale a pierdut teren în fața procedurilor medicale. Cercetarea de față a urmărit, pe de o parte, să identifice reprezentarea socială a bolii în rândul populației Rome și, pe de altă parte, să stabilească dacă aceasta a suferit modificări importante în ultimii ani, sub presiunea reprezentărilor sociale ale sănătății și bolii în rândul populației majoritare. În urma analizei rezultatelor interviurilor realizate putem concluziona că deși multe elemente ale nucleului central al reprezentării sociale sunt menținute, cum ar fi boala privită ca pedeapsă divină, superstițiile, metodele tradiționale de vindecare sau amprentele gândirii magice, se poate constata pătrunderea unor noi elemente în limbajul curent: cauzele bolilor din registrul medical, diagnostic sau tratamente medicale. În plus, un aspect important este modalitatea în care a evoluat relația medic-pacient, în prezent fiind aproape complet eliberată de constrângerile impuse de credințele tradiționale. Cuvinte-cheie: boală, sănătate, Roma, tradiție, aculturație